Body-wave seismic interferometry on passive seismic data for imaging CO2 reinjection at the Hellisheiði geothermal power plant, Iceland - Hassing, Sverre (author) (2022)
CO2 and H2S are reinjected at Hellisheiði, Iceland, to reduce the emissions of greenhouse gases. An active-source seismic campaign was done in July, 2021, to image the reinjection reservoir with various seismic methods for consecutive monitoring. At the same time, passive-source seismic data was recorded for imaging. We process this passive data with seismic interferometry. For this, an illumination analysis is performed to filter noise panels that are dominated by surface-wave noise and to keep panels dominated by body-wave noise. Afterwards, panels with near-vertical events are autocorrelated to retrieve a zero-offset section. The full set of selected panels is crosscorrelated to retrieve virtual shot records. These are processed with a simple reflection seismological processing workflow to obtain a stacked section. The results show that the autocorrelated zero-offset sections appear more noisy, but are characterised by higher frequencies, while the crosscorrelated stacked sections are characterised by a lower-frequency content and contain more dipping reflectors. The major, horizontal reflectors correspond between the two types of sections. A rudimentary interpretation of reflectors is done, based on the two types of sections and compared with a local geological model. This shows that the major lithological differences and the base of the Hengill volcano can be distinguished in the interpreted section. Applied Geophysics | IDEA League